Engineering and food for the 21th century - Welti-Chanes, Jorge (CRC Press LLC, 2011)
Engineering and Food for the 21st Century presents important reviews and up-to-date discussions of major topics relating to engineering and food. Internationally renowned contributors discuss a broad base of food engineering and related subjects, including research and prospective industrial applications. The first part begins with recent trends in food engineering and challenges for the future. It then presents important discussions of fundamental aspects of food engineering, including physical chemistry, mass transfer, food rheology, and food structure. Part 2 contains state-of-the-art presentations on thermal processing and packaging, minimal processing, emerging technologies, process control, biotechnology, and environmental factors associated with the processing of food.